Health Humanities - Crawford, P. author. aut Link
XI, 194 p.
Keywords: This is the first manifesto for Health Humanities worldwide. It sets out the context for this emergent and innovative field which extends beyond Medical Humanities to advance the inclusion and impact of the arts and humanities in healthcare, health and well-being.